The Hydration of Palm Oil Fuel Ash Modified Cement Paste at Different Curing Temperatures - Tanue, Nkwenti Flavious; Bondoh, Laurantine Momoh; Didier, Fokwa; Gilbert, Tchemou (European Journal of Applied Sciences, 2023)
As concrete production around the world continuously increases, the high levels of carbon dioxide emissions from cement manufacture have resulted in the growing interest in the field of supplementary cementitious materials (SCM). Palm oil fuel ash (POFA) has been proven to be a potential SCM. This study presents the partial replacement of cement with POFA in four different samples (0%, 5%, 10%, and 15%). It is aimed at investigating the influence of POFA on the physical properties and the hydration rate of cement paste at different temperature conditions (15° C, 28° C and 40° C). The hydration rate of the POFA-modified samples was determined by measuring the amount of hydration water consumed under the different curing conditions. Physical properties investigated included apparent density, specific density, fineness, soundness, consistency, and setting time tests. The results for physical properties showed that fineness varied from 0.5% for the control sample through 1.01% for the 5% POFA modified sample to 1.20% for the 15% POFA modified sample. For soundness, 10% and 15% POFA-modified samples are 50% sounder than both the 5% POFA-modified sample and the 0% sample. Meanwhile, both consistency and setting time were proven to be proportional to the increase in the POFA content of the sample. As for the rate of hydration, globally, the consumption of hydration water was proportional to curing temperature. However, at 15oC curing temperature, results varied perplexedly: dropping from 0% to 5% before increasing at 10%, and then dropping from 10% to 15%. At room temperature, a gradual continuous raise was recorded and a drop was witnessed only for the 15% sample. At 40° C curing temperature, it was instead a continuous drop of the hydration rate.